Literasi informasi masyarakat Desa Paseban, Kecamatan Kencong, Kabupaten Jember melalui budaya ‘marung’ - Anita Tri Widiyawati (Jurnal Kajian Informasi dan Perpustakaan, 2019)
The ‘marung’ culture is a custom of the people of Paseban village. The ‘marung’ activity is a means to relax after work, ward off feelings of loneliness by meeting neighbors, and sharing information. This becomes a potential for information literacy. The purpose of this study was to describe and analyze the factors underlying the formation of ‘marung’ culture and information literacy. The research method used qualitative research method. The data collection technique used was observation, interviews, and documentation. Data analysis steps in this study were (1) condensation of data, (2) presentation of data, and (3) drawing conclusions and verification. The data credibility test used: source triangulation, technique triangulation, and time triangulation. The result of this study showed ‘marung’ culture was formed based on the history of the village community to set strategies of defending themselves from Dutch colonialism by creating ‘cangkrukan’/gathering habits. After the Dutch colonial period ended, this ‘cangkrukan’ habit became attached to the village community. The ‘warung’ was considered the most strategic place for ‘cangkrukan’. This place can accommodate all people from various backgrounds to chat, have fun, establish ‘silaturahmi’/hospitality, relax from daily activities, and get the information needed. ‘Marung’ culture fulfills four cultural systems, namely: culture, social, personality, and organism. ‘Marung’ culture is very closely related to information literacy and Hubermas' theory of public space. The Paseban village community has implemented the IFLA information literacy standard in supporting its work, from the access, evaluation, to usage stages.